Assessment of Abundance, Diversity and Distribution of Freshwater Fishes of Tropical Rainforest Rivers, Southeast Nigeria - Adaka, G. S. (New Visions in Biological Science Vol. 7, 2021)
The present investigation was carried out on Oramiri-Ukwa River from January to December 2013 at three stations to study the fish diversity and distribution. The result of the investigation reveals the occurrence of 25 fish species belonging to 16 families. Fish samples were collected twice per month with the help of local fishers using hook and line, Gill net, cast net, Bagnet and local traps. Among the collected species Tilapia zilli was most abundant and highest accounting for 12.5% of the catch. Brycinus leuciscus, Fundulopanchax gardneri, Petrocephalus bane bane, Parailia pellucida, Malapterurus electricus, Polypterus senegalus, Parachanna africana and Shilbe mystus were the least in number. The values for Shannon-Weiner (H), Simpson’s index of dominance (D) and Simpson’s index of diversity (1-D) for the three stations were 0.0083, 0.0028, 0.084 and 0.027, 0.091, 0.281 and 0.973, 0.909, 0.719 respectively. The study findings showed that fish diversity and distribution of the study area is reducing with increased human activities. This is because the species composition of the study was lower than the results of other studies in the same water body. Autogenic and anthropogenic threats, and harmful practices which predispose fish species extinction along the floodplain and catchment area of the river should be subjected to environmental scrutiny to maintain the environmental health and integrity of the ecosystem.